Young patients with synchronous colorectal liver metastases. Issue 5 (25th April 2016) - Smith, James D.; Lowery, Maeve A.; Fell, David; Gallagher, David J.; Nash, Garrett M.; Kemeny, Nancy E.
Abstract : Background: An increasing proportion of patients are presenting with colorectal cancer at an early age. A proportion of these occur with genetic syndromes; however the majority present as sporadic. The purpose of this study is to investigate the prognosis and treatment of young patients with sporadic metastatic colorectal cancer. Methods: Following IRB approval, patients with sporadic metastatic colorectal cancer at 40 years or under were identified. Patient charts and pathology reports were analyzed retrospectively for clinical and pathological factors. Results: Three hundred and two patients were identified; 148 with liver metastases only, and 154 with extra‐hepatic disease. Five‐year overall survival was 19%, 28% for liver only disease, and 12% for extrahepatic disease. For patients with liver metastases only, factors associated with survival on univariable analysis included diagnosis in the 2000's, unilobular hepatic disease, smaller volume liver metastases, intrahepatic pump chemotherapy, resection of the primary, and resection of liver metastases. On multivariable analysis factors associated with survival included resection of the primary, resection of liver metastases, and diagnosis in the 2000's. Conclusion: Sporadic metastatic colorectal cancer in young patients appears to have a similar prognosis to that in older patients. The most significant prognostic factor was the ability to resect all sites of disease. J. Surg. Oncol. 2016;113:473–476 . © 2016 Wiley Periodicals, Inc.